PENERAPAN AKUNTANSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KELURAHAN WURYOREJO KECAMATAN WONOGIRI - Slamet Santosa; Dama Adi Purusa; Tulus Prijanto (JURNAL ILMIAH EDUNOMIKA, 2026)
The purpose of this study is to determine how accounting is applied in Micro, Small, and Medium Enterprises (MSMEs) and to determine what obstacles business actors face in implementing accounting. This study uses a descriptive qualitative research method by collecting data collected through questionnaires and interviews with business actors. MSME actors located in Wuryorejo Village, Wonogiri District are the objects in this study. A total of 61 data were successfully obtained and collected using a sampling method with a purposive sampling technique. The conclusion of this study shows that the majority of MSME actors already understand accounting even though the application of accounting and financial reports are presented manually and are still relatively simple. The obstacles faced by business actors include lack of time to prepare financial reports, the perception that preparing financial reports is difficult to understand, low business actors to improve the presentation of financial reports, and the lack of socialization or training on accounting in accordance with SAKEMKM.